2011
DOI: 10.1074/jbc.m111.249433
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gene Essential for the First Committed Step in the Biosynthesis of Bacteriochlorophyll c

Abstract: Bacteriochlorophylls (BChls) c, d, and e are the major chlorophylls in chlorosomes, which are the largest and one of the most efficient antennae produced by chlorophototrophic organisms. In the biosynthesis of these three BChls, a C-13 2 -methylcarboxyl group found in all other chlorophylls (Chls) must be removed. This reaction is postulated to be the first committed step in the synthesis of these BChls. Analyses of gene neighborhoods of (B)Chl biosynthesis genes and distribution patterns in organisms producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…c, d, e, and f: In the biosynthesis of BChl c, d, e, and f, the C13 2 -methoxycarbonyl group is removed by the BciC enzyme first. After the C-13 2 -methoxycarbonyl group of Chlide a is removed by the BciC enzyme, 3-vinyl-bacteriochlorophyllide d (3V-BChlide d) is formed (Liu andBryant 2011, Teramura et al 2016a). Then, the BchF or BchV enzyme hydrates the C-3 vinyl group to introduce the C-3 1 -hydroxyl group to form BChlide d , Teramura et al 2016b.…”
Section: Biosynthesis Of Bchl B and Bchl Gmentioning
confidence: 99%
“…c, d, e, and f: In the biosynthesis of BChl c, d, e, and f, the C13 2 -methoxycarbonyl group is removed by the BciC enzyme first. After the C-13 2 -methoxycarbonyl group of Chlide a is removed by the BciC enzyme, 3-vinyl-bacteriochlorophyllide d (3V-BChlide d) is formed (Liu andBryant 2011, Teramura et al 2016a). Then, the BchF or BchV enzyme hydrates the C-3 vinyl group to introduce the C-3 1 -hydroxyl group to form BChlide d , Teramura et al 2016b.…”
Section: Biosynthesis Of Bchl B and Bchl Gmentioning
confidence: 99%
“…The introduction of the 3 1 ‐hydroxy group is based on the hydration of the vinyl group to the 1‐hydroxyethyl group at the C3‐position by hydratases BchF and BchV . It has been reported that a BciC enzyme catalyzed the removal of a methoxycarbonyl group at the C13 2 ‐position, which reduced steric hindrance around the 13‐ketocarbonyl group . These chemical modifications provide more interactive 3 1 ‐hydroxy and 13‐carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequence analysis of this bacterium has already been completed, and parts of the biosynthetic pathways of BChl c have been revealed by genetic studies . Liu and Bryant first reported that a bciC gene affected removal of the C13 2 ‐methoxycarbonyl group in the biosynthesis of BChl c . Later, we examined the in vitro BciC enzymatic reaction, and revealed that the BciC enzyme catalyzed demethoxycarbonylation of chlorophyllide a (Chlide a ) to pyrochlorophyllide a (pyroChlide a ; Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…tepidum , a genetically tractable model organism of GSB [8], [9]. Following the recent discovery of an enzyme for removal of the 13 2 -methoxycarbonyl group from Chlide a , called BciC [10], all the genes encoding BChls c and d biosynthetic enzymes were revealed. However, only one step in the biosynthesis of BChl e has been unidentified, i.e., an enzyme producing a formyl group at the C7 position of bacteriochlorophyllide (BChlide) e (Fig.…”
Section: Introductionmentioning
confidence: 99%